BUSINESS-RELATED TERMINATION OF EMPLOYMENT CONTRACT IN VIEW OF JUDICIAL PRACTICE - Damir Juras; Anamarija Buzolić Mrklić (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
The employer may give the employee a business-related termination of employment contract if the need to perform a particular job ceases for economic, technical or organizational reasons. The employer must take into account the criteria prescribed by law then, he can specify additional criteria which will be taken into account when selecting worker which becomes redundant due to the termination of a particular job. A worker, whose employment contract has been terminated, is entitled to a notice period and severance pay. The paper contains extensive jurisprudence of procedure and conditions for giving a business-related termination of an employment contract. The court cannot valuate a validity of economic, technical or organizational changes’ implementation because it falls within autonomous authority of the employer, but the court is empowered to determine whether the reasons for business-related dismissal of a worker were justified and whether the employer terminated the employee’s employment contract in the manner prescribed by law.